Microsoft Office 2011 put a ribbon on it!. - Simon, Michael
The next version of Microsoft's flagship Mac products has finally starting to drink cocoa.
Keywords: MIcrosoft Office; Microsoft Office 2011.; Cocoa Office; Carbon programming; Mac